The C-4 stereochemistry of leucocyanidin substrates for anthocyanidin synthase affects product selectivity. - Turnbull, J; Nagle, M; Seibel, J; Welford, R; Grant, G; Schofield, C (2003)
Anthocyanidin synthase (ANS), an iron(II) and 2-oxoglutarate (2OG) dependent oxygenase, catalyses the penultimate step in anthocyanin biosynthesis by oxidation of the 2R,3S,4S-cis-leucoanthocyanidins. It has been believed that in vivo the products of ANS are the anthocyanidins. However, in vitro studies on ANS using optically active cis- and trans-leucocyanidin substrates identified cyanidin as only a minor product; instead both quercetin and dihydroquercetin are products with the distribution being dependent on the C-4 stereochemistry of the leucocyanidin substrates.